OFFICE LAYOUT ANALYSIS TO ACHIEVE EMPLOYEE PERFORMANCE (CASE STUDY AT PT. JASA RAHARJA PEKALONGAN BRANCH) - Shafa Chantika Pradesti Prabowo; Muhamad Nukha Murtadlo (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2025)
Phenomenon/Issue:Several issues have been identified, including limited service areas, open-plan workspaces without adequate partitions, suboptimal desk spacing, and a monotonous design. These conditions potentially disrupt employee comfort, workflow efficiency, and overall performance. Purpose:This study aims to analyze the role of office layout in achieving employee performance at PT. Jasa Raharja Pekalongan Branch, focusing on how spatial arrangement supports work effectiveness, coordination, and productivity. Research Methods:The research employs a qualitative approach using a case study method. Data were collected through direct observation of the office environment, in-depth interviews with employees and management, and documentation analysis. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the office layout’s impact on employee performance. Results:The findings indicate that the application of a combined open and closed office layout concept supports smoother workflows and effective inter-unit coordination. The layout aligns with office layout principles such as the shortest distance and proper work sequence. Nevertheless, several challenges remain, including insufficient desk spacing, limited design flexibility, and monotonous workspaces that may reduce employee motivation. Supporting physical factors such as lighting, air circulation, and acoustics are generally adequate and contribute positively to the work environment. Research Contributions: This study contributes practically by providing insights for organizational decision-makers in improving office layout design to enhance employee performance. Theoretically, it enriches the literature on office management and workplace design by emphasizing the importance of adaptive and functional office layouts in supporting employee effectiveness and productivity.